2016
DOI: 10.4238/gmr.15048705
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of obesity-associated gene STEAP4 in obese children

Abstract: ABSTRACT. The aim of this study was to investigate the expression and clinical significance of the obesity-associated gene STEAP4 in obese children. Fifty-three obese children and 33 children with a standard body weight (control) from our hospital were recruited to this study. The expression of STEAP4 mRNA and protein in the adipose tissue were detected by reverse transcriptase polymerase chain reaction and enzyme-linked immunosorbent assay, respectively, in order to analyze the relationship between STEAP4 mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…2011; Kim et al. 2015; Ozmen et al 2016; Xu et al 2016). Additionally, STEAP4 expression in both fat and muscle was reduced among the most insulin resistant individuals independent of BMI (Elbein et al.…”
Section: Regulatory Influences On Steap4 Expressionmentioning
confidence: 99%
“…2011; Kim et al. 2015; Ozmen et al 2016; Xu et al 2016). Additionally, STEAP4 expression in both fat and muscle was reduced among the most insulin resistant individuals independent of BMI (Elbein et al.…”
Section: Regulatory Influences On Steap4 Expressionmentioning
confidence: 99%
“…SNP rs408118325 on chromosome 4 maps near the STEAP4 metalloreductase gene (STEAP4, also known as STAMP2), a member of the TNF-a inducible proteinencoding family. STEAP4 encodes a metalloreductase abundantly expressed in human adipose tissue and involved in adipocyte development and metabolism, insulin sensitivity, and inflammation (Ohgami et al 2006;Zhang et al 2008;Catalan et al 2013;Ozmen et al 2016;Xu et al 2016). The two SNPs on chromosome 6, rs402128848 and rs401248376, are located in a region downstream of the C-terminal binding protein 1 gene (CTBP1).…”
Section: Gene Annotationmentioning
confidence: 99%
“…Known and putative upregulating factors include pro-inflammatory cytokines [7,13,32,33], nutrient intake [21], and acute cellular stress [13,21]. Downregulating factors of STEAP4 include obesity [2528], HbA1c/diabetic condition [26], and chronic inflammation. We discuss below how these putative competing regulatory factors may impact islet STEAP4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…A pair of studies showed that STEAP4 levels in adipocytes and white adipose tissue were increased in obesity [23,24], whereas other studies showed that STEAP4 was downregulated in obese people [2528]. In yet another study, STEAP4 gene expression in both fat and muscle was reduced among the most insulin resistant individuals independent of BMI [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation